Career Maturity In The Digital Age: Challenges And Solutions For Guidance Services In High Schools - Muhammad Riza Darwin; Ardilla Indah Mustia; Hani Nurrofifah (Universitas Islam Bunga Bangsa Cirebon, 2025)
Career maturity is an important aspect of student development in high school, as they begin to make decisions that affect their future. However, in this digital era, students are faced with various new challenges that affect their career maturity. This study aims to explore the challenges and solutions faced by guidance services in helping students develop career maturity in the digital era. The systematic literature review in this study followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, investigating the impact of career maturity and guidance services on high school students in the digital era. Key areas explored include the role of digital skills, social cognitive career theory (SCCT), and the Technology Acceptance Model (TAM) in career guidance. The findings indicate that digital technology enhances career maturity. While the main challenges include low student awareness of digital skills and lack of technology support. Then there are barriers to technology acceptance, such as perceived difficulty of use and limited technical support. To overcome this, the results of the review suggest integrating digital skills training and tailored support for students and counselors. This approach aims to foster career maturity in students, which is in line with the demands of an increasingly digital workforce.